Methodology to determine the social value of cultural heritage: The case of classical arts in Bahía Blanca, Argentina - Leonardi, Viviana (2026)
The recognition of the social value of cultural heritage allows us to take advantage of its effects on human and social development. The objective of this work is to design and apply a tool that contributes to its measurement. A methodological framework based on the Social Multicriteria Evaluation (Munda, 2004) is proposed and applied to the case of a local institution dedicated to classical art (ballet, orchestral and choral music) in Bahía Blanca, Argentina. Primary information collected during 2022 is mainly used. An average social value is verified, based on the feeling of identity and appropriation. Likewise, the need to strengthen the continuity of said heritage is evident.